Social Status and Risk-Taking in a Model of Occupational Choice - Christiane Clemens (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2002)
This paper is concerned with occupational choice under risk, where agents care about their social status. It is motivated by recent developments in the 'New Economy', which indicate that status preferences possibly provide an explanation for the observed shift towards entrepreneurial risk-taking. We find a positive tradeoff between status, risk and the attitude towards risk in a risk-averse society, where a higher proportion of agents chooses the entrepreneur class, compared to a status-neutral economy. We derive conditions for an optimal agree of individual status valuation. Although the population shares of laborers and entrepreneurs, and expected incomes converge towards the efficient values of the risk-neutral economy, when preferences for status increase, this is not true for expected utility, which asymptotically falls back to the equilibrium value of the status-neutral society. A second-best welfare maximum corresponds to an inefficient distribution of agents over the two types of occupations.
Keywords: D5; D8; D9; 330; risk-taking; occupational choice; social status